Development and implementation of statistical tools to be used in phenomenological analyses in particle physics (2017)
This work presents the development of scripts for the phenomenology group at Universidad de los Andes. The aim of these scripts is to carry out hypothesis tests for discovery, taking as inputs histograms for signal points and background contributions common to said signals. It also takes histograms for collected experimental data, but in the case that data is not available, pseudo-data is generated for each signal point by adding it to the total background. The scripts were fully tested using simulated events from a published phenomenological analysis of the High Energy Physics group at Universidad de los Andes. They have also been fully documented and are available online in a GitHub repository